2014
DOI: 10.1111/jon.12143
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of A Qualitative Brain MRI Scoring System After Cardiac Arrest

Abstract: A qualitative MRI scoring system helps assess hypoxic-ischemic brain injury severity following cardiac arrest and may provide useful prognostic information in comatose cardiac arrest patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 21 publications
0
72
2
Order By: Relevance
“…Previous studies have shown that injury to specific brain regions, such as the cortical gray matter and deep gray structures, correlated with poor patient outcomes [27,28]. In this study, specific regions of interest were not analyzed independently of the whole brain quantitative analysis though future work will incorporate this analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that injury to specific brain regions, such as the cortical gray matter and deep gray structures, correlated with poor patient outcomes [27,28]. In this study, specific regions of interest were not analyzed independently of the whole brain quantitative analysis though future work will incorporate this analysis.…”
Section: Discussionmentioning
confidence: 97%
“…MR imaging morphologic analysis was accomplished by using two validated scores on the basis of a visual rating (23,24). In the system proposed by Hirsch et al (24), developed in a similar population with CA, the anatomic location and degree of signal abnormality measure extensively validated in patients with CA that describes five levels of functional ability: 1, good cerebral performance (ie, alert, able to work); 2, moderate disability (ie, conscious, independent in most activities of daily living); 3, severe disability (ie, conscious but dependent in most activities of daily living); 4, coma or vegetative state; and 5, brain death. Patients with a cerebral performance category score of 1-2 were classified as having a favorable outcome (FO) and those with a cerebral performance category score of 3-5 were classified as having an unfavorable outcome.…”
Section: Image Processingmentioning
confidence: 99%
“…Anoxia-induced brain swelling in the acute phase after CA is associated with diffuse brain damage in thalamus, basal ganglia, cerebellum, hippocampus, frontal, and parietal cortices [24][25][26]. Neural degeneration over time in these regions has been described in nonsurvivors of CA [27,28]. Because neural processing in hippocampal [29][30][31] and frontoparietal regions [32,33] plays a crucial role for sensory-memory trace formation and violation detection, the progression of auditory discrimination measured in our study might directly reflect the progression of anoxia-induced functional impairment in these brain regions.…”
Section: Brain Mechanisms Of Auditory Discrimination Progressionmentioning
confidence: 99%